2020
DOI: 10.1038/s41467-020-15237-5
|View full text |Cite
|
Sign up to set email alerts
|

OXPHOS remodeling in high-grade prostate cancer involves mtDNA mutations and increased succinate oxidation

Abstract: Rewiring of energy metabolism and adaptation of mitochondria are considered to impact on prostate cancer development and progression. Here, we report on mitochondrial respiration, DNA mutations and gene expression in paired benign/malignant human prostate tissue samples. Results reveal reduced respiratory capacities with NADH-pathway substrates glutamate and malate in malignant tissue and a significant metabolic shift towards higher succinate oxidation, particularly in high-grade tumors. The load of potentiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
91
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(102 citation statements)
references
References 76 publications
(104 reference statements)
3
91
2
Order By: Relevance
“…Beyond the Warburg effect, a metabolic shift towards complex II-dependent succinate oxidation was recently described as an adaptive mechanism to compensate for OXPHOS dysfunction in high-grade prostate cancers, mutant for the ND1 subunit of complex I [ 54 ]. As a response to the inhibition of glutamate and malate oxidation and to the subsequent electron transport loss across complex I, ND1-mutant cancer cells were found to produce ATP by aerobic respiration through complex II-mediated succinate oxidation [ 54 ]. This metabolic reprogramming was associated with shorter patient survival, highlighting the critical role of complex II and succinate in malignancies associated with complex I dysfunction [ 54 ].…”
Section: Effects Of Mutations In the Subunits Of Complexes I And Imentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond the Warburg effect, a metabolic shift towards complex II-dependent succinate oxidation was recently described as an adaptive mechanism to compensate for OXPHOS dysfunction in high-grade prostate cancers, mutant for the ND1 subunit of complex I [ 54 ]. As a response to the inhibition of glutamate and malate oxidation and to the subsequent electron transport loss across complex I, ND1-mutant cancer cells were found to produce ATP by aerobic respiration through complex II-mediated succinate oxidation [ 54 ]. This metabolic reprogramming was associated with shorter patient survival, highlighting the critical role of complex II and succinate in malignancies associated with complex I dysfunction [ 54 ].…”
Section: Effects Of Mutations In the Subunits Of Complexes I And Imentioning
confidence: 99%
“…As a response to the inhibition of glutamate and malate oxidation and to the subsequent electron transport loss across complex I, ND1-mutant cancer cells were found to produce ATP by aerobic respiration through complex II-mediated succinate oxidation [ 54 ]. This metabolic reprogramming was associated with shorter patient survival, highlighting the critical role of complex II and succinate in malignancies associated with complex I dysfunction [ 54 ].…”
Section: Effects Of Mutations In the Subunits Of Complexes I And Imentioning
confidence: 99%
“…In contrast, the presence of heteroplasmy affecting functionally relevant sites might be an indication for disease and is found in many human tumors [ 10 ]. In fact, our group could demonstrate the involvement of mtDNA mutations in several types of cancer [ 11 , 12 , 13 , 14 ]. Several studies reported a potential role of mtDNA mutations in OSCC [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, RNA-seq analysis of prostate tissues shows remarkable enrichment of OXPHOS-related genes in CRPC ( 66 ). Moreover, a study analyzing substrate-specific OXPHOS capacities using primary human prostate tissues revealed that the malignant tissues exhibits a significant metabolic shift toward higher succinate oxidation by complex II, particularly in high-grade prostate tumors ( 67 ).…”
Section: Oxphos With Lncrnamentioning
confidence: 99%